A novel nomogram to predict futile recanalization in patients with acute ischemic stroke undergoing mechanical thrombectomy - Lai, Cheng-cai; Yao, Yin-dan; Li, Xia; Liu, Ao-fei; Li, Chen; Liu, Yun-e; Jiang, Chang-chun; Zhang, Ying-ying; Jin, Min; Lv, Jin; Jiang, Wei-jian (Frontiers in Neurology, 2024)
Background and objective Futile recanalization (FR) is defined as patients with acute ischemic stroke (AIS) due to large vessel occlusion who still exhibits functional dependence although undergoing successful mechanical thrombectomy (MT). We aimed to develop and validate a simple nomogram for predicting the probability of FR after MT treatment in AIS patients. Methods Clinical data of AIS patients in the Jrecan clinical trial in China from March 2018 to June 2019 were collected as the derivation set (n = 162). Meanwhile, clinical data of AIS patients who underwent MT in Baotou Central Hospital and Ningbo No.2 Hospital from 2019 to 2021 were collected as the validation set (n = 170). Multivariate logistic regression analysis was performed for all variables that had p < 0.2 in the univariate analysis in the derivation set. The independent risk factors of FR were further screened out and a nomogram was constructed. The performance of the nomogram was analyzed in the derivation and validation set using C-index, calibration plots, and decision curves. Results No significant difference in FR rate was detected between the derivation set and the validation set [88/162 (54.32%) and 82/170 (48.23%), p = 0.267]. Multivariate logistic regression analysis showed that age ≥ 65 years old (OR = 2.096, 95%CI 1.024–4.289, p = 0.043), systolic blood pressure (SBP) ≥ 180 mmHg (OR = 5.624, 95%CI 1.141–27.717, p = 0.034), onset to recanalization time (OTR) ≥ 453 min (OR = 2.759, 95%CI 1.323–5.754, p = 0.007), 24 h intracerebral hemorrhage (ICH; OR = 4.029, 95%CI 1.844 ~ 8.803, p < 0.001) were independent risk factors for FR. The C-index of the nomogram of the derivation set and the verification set were 0.739 (95%CI 0.662~0.816) and 0.703 (95%CI 0.621~0.785), respectively. Conclusion The nomogram composed of age, SBP, OTR, and 24 h ICH can effectively predict the probability of FR after MT in AIS patients.